Transcription module for voice commands in automatic devices environment - A. Юдов; K. Остапченко (Adaptivni Sistemi Avtomatičnogo Upravlinnâ, 2022)
The purpose of this work is to verify the effectiveness of the module of transcription of voice commands in a multilingual environment by determining the parameters of the voice signal during the operation of the module. An analysis of approaches to solving the problem of speech recognition in the flow of audio data, among which the emphasis is on the recognition of the speaker's voice signal. The study uses voices from Google's database in various languages to improve the implementation of voice commands for automatic “turn on” / ”turn off” equipment. Voice commands are performed in 9 random languages, depending on the availability of the Google Voice database using the recognition module. The influence of volume and distance on the performance of the voice recognition module is analyzed. The effectiveness and influence of the choice of command language from the distance between the microphone and the speaker in the range of approximately 5 cm, 10 cm and 15 cm, as well as the volume of voice commands in Google Voice at 30%, 50% and 100%.